2020
DOI: 10.1093/mnras/staa769
|View full text |Cite
|
Sign up to set email alerts
|

An ALMA survey of the SCUBA-2 CLS UDS field: physical properties of 707 sub-millimetre galaxies

Abstract: We analyse the physical properties of a large, homogeneously selected sample of ALMA-located sub-millimetre galaxies (SMGs) detected in the SCUBA-2 Cosmology Legacy Survey 850-µm map of the UKIDSS/UDS field. This survey, AS2UDS, identified 707 SMGs across the ∼ 1 deg 2 field, including ∼17 per cent which are undetected in the optical/near-infrared to K 25.7 mag. We interpret the UV-to-radio data of these systems using a physically motivated model, magphys and determine a median photometric redshift of z = 2.61… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

77
533
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 251 publications
(623 citation statements)
references
References 166 publications
(297 reference statements)
77
533
7
Order By: Relevance
“…Interestingly there are reported DSFGs at > 4¯5 with increasing flux densities with increasing wavelength resembling jet emission (Ivison et al 2016;Riechers et al 2017) . However, given the likely rarity of such sources (the redshift distribution of DSFGs spans = 1-3, Chapman et al 2005;Dudzevičiūtė et al 2020, observed at similar wavelengths) we consider this possibility fairly unlikely. Now considering the geometry, we identify seven fields with pairs of submillimetre detections that are diametrically opposite each other along a line which passes trough the calibrator.…”
Section: Identifying Jet Emission From Calibratorsmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly there are reported DSFGs at > 4¯5 with increasing flux densities with increasing wavelength resembling jet emission (Ivison et al 2016;Riechers et al 2017) . However, given the likely rarity of such sources (the redshift distribution of DSFGs spans = 1-3, Chapman et al 2005;Dudzevičiūtė et al 2020, observed at similar wavelengths) we consider this possibility fairly unlikely. Now considering the geometry, we identify seven fields with pairs of submillimetre detections that are diametrically opposite each other along a line which passes trough the calibrator.…”
Section: Identifying Jet Emission From Calibratorsmentioning
confidence: 95%
“…These galaxies are radio bright because the line of sight coincides with the direction of the jet and not because they are particularly radioluminous or massive (De Breuck et al 2002;Seymour et al 2007). However, most DSFGs are at z 1 (Dudzevičiūtė et al 2020) while the calibrators are mostly below z ∼ 1 with a tail to z ∼ 3 (see Table 1). Therefore, it is less likely that the calibrator and the DSFGs are physically associated.…”
Section: Clustering Of Sourcesmentioning
confidence: 99%
“…The extreme infrared luminosities observed in these submillimeter galaxies (SMGs) suggest that they are dusty and considered to be among the most intensively star-forming sources in the universe (Smail et al 1997;Barger et al 1998Barger et al , 1999Hughes et al 1998;Eales et al 1999). SMGs appear to have a redshift distribution peaking at z ; 2.5 with the majority of them at z=1.5-3.5 (Barger et al 2000;Chapman et al 2003Chapman et al , 2005Pope et al 2006;Aretxaga et al 2007;Wardlow et al 2011;Michałowski et al 2012bMichałowski et al , 2017Yun et al 2012;Simpson et al 2014Simpson et al , 2017Koprowski et al 2016;Danielson et al 2017;Dunlop et al 2017;Stach et al 2019;Dudzevičiūtė et al 2020), occupying the same putative peak epoch of unobscured star formation (Madau & Dickinson 2014) and active galactic nucleus (AGN) activity (Schmidt et al 1995;Hasinger et al 2005;Wall et al 2008;Assef et al 2011). The total infrared luminosities (L IR ; 8-1000 μm) of SMGs are similar to local ultra-luminous infrared galaxies (Sanders et al 1988;Sanders & Mirabel 1996;Farrah et al 2001;Armus et al 2009), reaching values greater than a few times 10 12 L ☉ or even higher than 10 13 L ☉ for some of the brightest sources.…”
Section: Introductionmentioning
confidence: 99%
“…The total infrared luminosities (L IR ; 8-1000 μm) of SMGs are similar to local ultra-luminous infrared galaxies (Sanders et al 1988;Sanders & Mirabel 1996;Farrah et al 2001;Armus et al 2009), reaching values greater than a few times 10 12 L ☉ or even higher than 10 13 L ☉ for some of the brightest sources. This corresponds to star formation rates (SFRs) ranging from around 100 M ☉ yr −1 to more than 1000 M ☉ yr −1 (Hainline et al 2011;Barger et al 2012;Swinbank et al 2014;da Cunha et al 2015;Simpson et al 2015;Dudzevičiūtė et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation